2017
DOI: 10.1186/s12906-017-1575-9
|View full text |Cite
|
Sign up to set email alerts
|

Korean mistletoe (Viscum album coloratum) extract regulates gene expression related to muscle atrophy and muscle hypertrophy

Abstract: BackgroundKorean mistletoe (Viscum album coloratum) is a semi-parasitic plant that grows on various trees and has a diverse range of effects on biological functions, being implicated in having anti-tumor, immunostimulatory, anti-diabetic, and anti-obesity properties. Recently, we also reported that Korean mistletoe extract (KME) improves endurance exercise in mice, suggesting its beneficial roles in enhancing the capacity of skeletal muscle.MethodsWe examined the expression pattern of several genes concerned w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Under cachexic conditions, myo-proteins undergo ubiquitin modification by E3 ubiquitin ligases and proteasome-dependent degradation [5,6]. Thus, increased expression of E3 ubiquitin ligases indicate the progress of muscle atrophy accompanied by myofibrillar and intracellular proteins breakdown [17,30]. Bodine et al have shown that MAFbx or MuRF1-deficient mouse can overcome muscle atrophy, whereas MAFbx overexpressing myoblasts exhibit retardation in myotube formation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Under cachexic conditions, myo-proteins undergo ubiquitin modification by E3 ubiquitin ligases and proteasome-dependent degradation [5,6]. Thus, increased expression of E3 ubiquitin ligases indicate the progress of muscle atrophy accompanied by myofibrillar and intracellular proteins breakdown [17,30]. Bodine et al have shown that MAFbx or MuRF1-deficient mouse can overcome muscle atrophy, whereas MAFbx overexpressing myoblasts exhibit retardation in myotube formation [31].…”
Section: Discussionmentioning
confidence: 99%
“…In C2C12 cells, as well as in denervated mice, mistletoe decreased gene expression of Atrogin-1. On the contrary, in C2C12 cells, mistletoe increased mRNA expression of PGC-1α, GLUT-4, and SREBP-1c genes related to the inhibition of muscle atrophy and related to the induction of muscle hypertrophy by regulating the expression of Atrogin-1and Murf1 (Jeong et al 2017). Lim et al (2017) conducted randomized controlled trial confirming that supplementation with Korean mistletoe extract and exercise affects muscle mass and functional capabilities.…”
Section: Activity Against Muscle Declinementioning
confidence: 94%
“…Supplementation with mistletoe might be effective against age-related decline in muscle mass (Table 2). An in vitro study showed that an aqueous extract of Korean mistletoe caused higher phosphorylation of AKT in C2C12 cells (mouse myoblast cell line), suggesting that mistletoe has an effect on the regulation of the muscle mass through the activation of the AKT/mTOR (protein kinase B/ mammalian target of rapamycin) signalling pathway (Jeong et al 2017) (Fig. 9).…”
Section: Activity Against Muscle Declinementioning
confidence: 99%
“…A 4-week supplementation of KME can improve skeletal muscle weight and strength, in denervation-induced atrophy mice. The expression of the skeletal muscle protein degradation genes (Murf1 and Atrogin1) were downregulated by KME treatment, hinting at a possible mechanism in preventing skeletal muscle wasting (Jeong et al, 2017).…”
Section: Anti-atrophymentioning
confidence: 96%